2018
DOI: 10.1159/000488418
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Fine Particulate Matter Causes Hypertension Due to Impaired Renal Dopamine D1 Receptor in Offspring

Abstract: Background/Aims: Adverse environment in utero can modulate adult phenotypes including blood pressure. Fine particulate matter (PM2.5) exposure in utero causes hypertension in the offspring, but the exact mechanisms are not clear. Renal dopamine D1 receptor (D1R), regulated by G protein-coupled receptor kinase type 4 (GRK4), plays an important role in the regulation of renal sodium transport and blood pressure. In this present study, we determined if renal D1R dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Blood lipids, including total cholesterol and triglycerides, were measured by the ELISA kit (Jiancheng, Nanjing, China). The blood pressure and heart rate were also measured at 4, 8, 12, 16, 20, and 24 weeks of age in conscious rats using a computerized noninvasive tail-cuff manometry (BP-98A; Softron, Tokyo, Japan) as described in previous studies [22,23]. Blood pressure and heart rate were measured five times between 3:00–5:00 PM; the average of the five measurements was used in the calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Blood lipids, including total cholesterol and triglycerides, were measured by the ELISA kit (Jiancheng, Nanjing, China). The blood pressure and heart rate were also measured at 4, 8, 12, 16, 20, and 24 weeks of age in conscious rats using a computerized noninvasive tail-cuff manometry (BP-98A; Softron, Tokyo, Japan) as described in previous studies [22,23]. Blood pressure and heart rate were measured five times between 3:00–5:00 PM; the average of the five measurements was used in the calculations.…”
Section: Methodsmentioning
confidence: 99%
“…The computerized non-invasive tail-cuff manometry system (MODEL MK-2000, Muromachikikai Co. Ltd, Tokyo, Japan) was used to measure the systolic and diastolic blood pressure of conscious SD rats (18). The blood pressures were measured for 15 min between 8:00 AM and 12:00 PM in rats individually restrained in a clear acrylic restrainer at an ambient temperature of 37°C.…”
Section: Non-invasive Blood Pressure Measurementmentioning
confidence: 99%
“…To investigate the effect of a low salt diet on the blood pressure, SD rats were randomly divided into low salt (0.04% NaCl) diet group and normal salt (0.4% NaCl) diet group. After 8 weeks, the systolic and diastolic blood pressures of conscious SD rats were measured using a non-invasive tail-cuff manometry system (18). The results showed that the blood pressures of the low salt diet group (SBP: 143 ± 6.0 mmHg, DBP: 92 ± 7.4 mmHg) were significantly higher than the normal salt diet group (SBP: 121 ± 7.0 mmHg, DBP: 74 ± 8.5 mmHg) (Figures 1(a) and 1(b)).…”
Section: Low Salt Diet Increases the Blood Pressure Of Sd Ratsmentioning
confidence: 99%
“…2017). Evidence of prenatal reprogramming by PM2.5 also extends to the renal system; research in rats suggests that adult offspring of dams exposed to PM2.5 via oropharyngear drip during pregnancy have impaired renal dopamine D1 receptor-mediated sodium excretion and increased blood pressure (Ye et al. 2018).…”
Section: Discussionmentioning
confidence: 99%